Adaptation of Bivalve Molluscs to Environmental Conditions in the Coastal Region of El Jadida (Morocco): Case of Mytilus Galloprovincialis - Aafaf, Essedaoui; Abdelfettah, Messaoudi; Abdesslam, Ferssiwi; Redouane, Massar; Abdelali, Bitar (European Scientific Journal, ESJ, 2017)
The aim of this study is to assess the impact of industrial pollution on the growth and reproduction of the mussel Mytilus galloprovincialis from coastal region of El Jadida (Morocco). To this aim, three stations (S1, S2 and S3) are chosen according to their proximity to the industrial effluents of the chemical complex. The seawater and mussels (N = 100/ station) samples have been randomly and monthly collected for a period of 6 months (February-July 16). Mussels are distributed in 6 classes of size and measures of condition index and gonadic index are performed in the most common size classes. The results of the analysis of physicochemical parameters of the water show spatio-temporal variations with an acidic pH, high temperature and low salinity in the station near of industrials effluents. Regarding condition index and the gonadic index, there is no significant difference between the mussels collected from the reference station (S2) and the polluted station (S3). This can be explained partly by the adoption of a strategy of adaptation to the environmental stress caused by the industrial pollution.